КУЛЬТИВАТОРДЫҢ ЖУМЫС ОРГАНЛАРЫ БОЙЫНША ОРЫНЛАНҒАН ИЛИМИЙ ЖУМЫСЛАРҒА ШОЛЫУ - Утемуратова, Д. (FAN va JAMIYAT, 2016)
The article is devoted to the review of the scientific research works on the issues of study of the working parts of a cultivator. The author of the article shows the functions of the working parts of a cultivator on the basis of concrete examples.